2010
DOI: 10.1111/j.1540-5982.2009.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the wage patterns of Canadian less skilled workers: the role of implicit contracts

Abstract: We examine the wage patterns of Canadian less skilled male workers over the last quarter century by organizing workers into job entry cohorts. We find entry wages for successive cohorts declined until 1997, and then began to recover. Wage profiles steepened for cohorts entering after 1997, but not for cohorts entering in the 1980s -a period when start wages were relatively high. We argue that these patterns are consistent with a model of implicit contracts with recontracting in which a worker's current wage is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…There is a large body of literature suggesting that low‐skilled workers have fared poorly in the last 25 to 30 years (e.g., Frenette, Green, and Milligan 2007; Green and Townsend 2010). This extensive literature has tended to focus on wages (or income) as the outcome of interest.…”
Section: Further Explorationmentioning
confidence: 99%
“…There is a large body of literature suggesting that low‐skilled workers have fared poorly in the last 25 to 30 years (e.g., Frenette, Green, and Milligan 2007; Green and Townsend 2010). This extensive literature has tended to focus on wages (or income) as the outcome of interest.…”
Section: Further Explorationmentioning
confidence: 99%
“… Green and Townsend () show that when wages for high school or less‐educated men are organized by job cohort (defined by when they started their job), the starting wages for cohorts entering jobs in the early 1980s are on the order of 20% above those for cohorts entering in the 1990s or later. Moreover, the real wages of the older cohorts are maintained even while those of the new cohorts are declining.…”
mentioning
confidence: 99%
“…Green and Townsend (2010) show that when wages for high school or less-educated men are organized by job cohort (defined by when they started their job), the starting wages for cohorts entering jobs in the early 1980s are on the order of 20% above those for cohorts entering in the…”
mentioning
confidence: 99%
“…24 Williams (2005) suggested that the net return to 10 years of tenure to be 1 1 percent. Green and Townsend (2010) studied the wage-tenure profiles for unskilled workers and found that workers with higher job tenure are less impacted by economic variations. McDonald and Worswick (1998) introduced tenure variables and the interaction ofjob tenure with immigrants' cohorts to allow for the job tenure effect in immigrant wage studies.…”
Section: Mobility Level Of Workers Between Employersmentioning
confidence: 99%
“…The most recent research by Green and Townsend (2010) focuses on Canadian male workers with high school education or less. Evidence is presented of a long downward trend in the real wages of less-skilled workers.…”
mentioning
confidence: 99%